A morphometric approach into mackerel (Rastrelliger spp.) diversity in Fisheries Management Area 711 as a management base. Issue 1 (April 2021) - Wardiatno, Y; Aziz, A; Zairion,; Meilana, L; Hakim, A A
Abstract: Rastrelliger spp. is a small pelagic fish with important ecological and economic value in Indonesia. Genus Rastrelliger has three species with different distribution patterns, so they have diversity in morphology and populations in several waters. The study aimed to analyze the morphometric diversity of mackerel ( Rastrelliger spp.) in Bintan, Bangka, and Ketapang waters (Fisheries Management Area 711) using standard morphometric methods and truss network analysis. 310 samples were collected from all locations based on simple random sampling. The growth pattern of Rastrellliger spp. was negative allometric in each location. The cluster analysis showed that the mackerel populations from Ketapang and Bangka formed one group, while Bintan tended to be different. Based on the discriminant analysis, there are overlapping populations between Ketapang and Bangka. The difference of morphometric characters on mackerel ( Rastrelliger spp.) can indicate different species, so there is potential for more than one population or stock in FMA 711.